Short communication on "Updated geological map of the Borborema Province, northeastern Brazil" - SANTOS, Frank Gurgel (2023)
The Borborema Province (BP), Northeast Brazil, represents one of the main structural provinces of Brazil, and underwent numerous studies, including projects conducted by the Geological Survey of Brazil - SGB/CPRM, especially focusing on systematic geological mapping. As a result, a large part of the BP is covered by geological mapping at the scale 1:100,000 and, however, did not have an appropriate integrated map that represents the current level of knowledge of this geological object. The project Geology and Mineral Potential of the Borborema Province was conducted by the SGB with the objective of making available products to leverage the geological knowledge of the BP. In 2021 it was made available the regional geological integration map, besides the respective vector data, which represents the state-of-the-art of the geological knowledge in the province, also containing information about mineral resources and geochronological data. This short communication presents information about the making of the Geological Map of Borborema Province, at the scale of 1:500,000 (Appendix 1).